RANCANG BANGUN ALAT KEHADIRAN OTOMATIS MENGGUNAKAN QRCODE DILENGKAPI DENGAN PENGUKUR SUHU BADAN DAN CUCI TANGAN - Dina Rahmawati, Ni Putu; Diafari Djuni H, I Gst A. Komang; Setiawan, Widyadi (Jurnal SPEKTRUM; Vol 10 No 1 (2023): Jurnal SPEKTRUM, 2023)
At the beginning of 2020 the world was shocked by the outbreak of the corona virus which infected almost all countries in the world. WHO since January 2020 has declared the world to be in a global emergency related to the Covid-19 virus. As a preventive measure, every public facility and shop must have hand washing equipment, check body temperature before entering the room so that people who have a high temperature must go to the doctor, this also applies to schools to prevent new clusters in the educational environment. In this journal, the presence of a QRCODE-based automatic tool using the MLX90614 temperature sensor to measure body temperature is connected to the Arduino UNO microcontroller and displayed on the LCD in the form of temperature sensor measurement data and OLED displays QRCODE data scanned using the presence application. The Sensor Module MLX90614 has an IR sensitive thermopile detector chip and a signal conditioning ASIC integrated in the sensor packing model TO-39. The signal conditioning in the form of a low noise amplifier, 17-bit ADC and a powerful DSP unit achieves the accuracy and high resolution of the thermometer. The attendance application is made forAndroid smartphones, students can scan the QRCODE to make attendance through an application on an Android smartphone, so using the QRCODE can speed up and simplify receiving information obtained on the smartphone application. Testing of the prototype tool was carried out at Pupuan One Roof Public Middle School 6, a trial was carried out with several students, the lowest measurement difference was 0.2 °C and the highest was 0.5 °C with a measurement distance of 5 cm from the sensor surface. The prototype can be used for attendance from checking temperature, washing hands and making attendance from a smartphone then the data is submitted and stored in the Firebase database.